Coverage of employment protection legislation - Mariya Aleksynska; Friederike Eberlein (IZA Journal of Labor Policy, 2016)
This paper documents the construction of a novel database on coverage of workers by employment protection legislation (EPL), across over 90 countries around 2010. Coverage is shown to be an important, yet largely neglected, aspect of employment protection institution, complementing our knowledge about the protection level afforded by this institution. Our findings suggest that while coverage of employees across the world is generally high, coverage of all employed workers exhibits a substantial variation across countries in different regions and at different stages of development, reflecting the fact that wage employment still represents only a small proportion of total employment in developing countries. Our preliminary results indicate that there may not necessarily be a trade-off between the level of protection afforded by EPL and the proportion of workers legally covered by these rules. The results suggest that failure to account for EPL coverage in studies looking at aggregate effects of EPL level may lead to overestimating the importance of EPL, with this overestimation being especially large in lower-income countries.
Keywords: J5; J8; 330; Employment protection legislation; EPL; Coverage; Labor market institutions; Labor market indicators